2015
DOI: 10.1016/j.jbtep.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive examination of delayed emotional recovery in borderline personality disorder

Abstract: Background and Objectives Despite growing attention to emotion processes in borderline personality disorder (BPD), little research has examined delayed emotional recovery (i.e., long-lasting emotions after the termination of an emotionally evocative stimulus) in this population. The extant data on delayed emotional recovery in BPD are limited by a lack of assessment across a range of indices and emotions. The present study addresses these gaps by comparing emotional recovery between individuals with BPD, socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
2
21
0
1
Order By: Relevance
“…Reduced vagal functioning was also associated with increased anger ruminations following an anger provocation (e.g., receiving an unfair offer; Vögele, Sorg, Studtmann, & Weber, ). Finally, in a clinical sample of borderline and socially anxious individuals, as compared to controls, lower RSA was associated with greater emotional reactivity in response to an anger‐inducing film (Fitzpatrick & Kuo, ). Although not specific to depression, these findings suggest that anger regulation (i.e., reactivity and recovery) may be associated with low RSA and RSA withdrawal.…”
mentioning
confidence: 99%
“…Reduced vagal functioning was also associated with increased anger ruminations following an anger provocation (e.g., receiving an unfair offer; Vögele, Sorg, Studtmann, & Weber, ). Finally, in a clinical sample of borderline and socially anxious individuals, as compared to controls, lower RSA was associated with greater emotional reactivity in response to an anger‐inducing film (Fitzpatrick & Kuo, ). Although not specific to depression, these findings suggest that anger regulation (i.e., reactivity and recovery) may be associated with low RSA and RSA withdrawal.…”
mentioning
confidence: 99%
“…This pattern of findings may help to clarify a mixed literature on the relationship between BPD and prolonged distress recovery (e.g., Feliu-Soler et al, 2013;Fitzpatrick & Kuo, 2015;Gratz et al, 2010;Jacob et al, 2009;Scheel et al, 2013): positive findings may reflect instances in which ruminative responses were deployed. Specifically, though BPD features directly predicted heightened distress reactivity, their effect was indirect for distress recovery via ruminative response deployment and the dispositional tendency to ruminate (or to brood).…”
Section: Discussionmentioning
confidence: 74%
“…For example, following a mood induction during which participants were instructed to identify with an embarrassed protagonist under evaluation, women with BPD reported stronger feelings of shame across an 8-min follow-up period relative to depressed and healthy control participants (Scheel et al, 2013). On the other hand, BPD patients did not differ from their depressed, anxious, or healthy counterparts in the time course of NA following exposure to unpleasant images (Feliu-Soler et al, 2013) or evocative film clips that have been previously validated to elicit discrete emotional states (Fitzpatrick & Kuo, 2015). However, findings from laboratory studies are mixed, with some failing to note differences in the time course of distress recovery following an interpersonal betrayal-themed story between women diagnosed with BPD, depression, and their healthy peers (Jacob et al, 2009), and others observing more enduring feelings of shame among those with BPD in response to computerized negative performance feedback within a failure paradigm (Gratz et al, 2010).…”
Section: Bpd and Distress Recoverymentioning
confidence: 88%
See 1 more Smart Citation
“…Still other studies found that those with BPD reported higher negative emotions at baseline (Jacob et al, 2009; Kuo & Linehan, 2009; Reitz et al, 2012), but no differences in reactivity than controls. In addition, whereas some research revealed that, compared with healthy participants, those with BPD took longer to recover emotionally (Reitz et al, 2012) or evidenced more prolonged experiences of specific emotions, such as shame (Gratz, Rosenthal, Tull, Lejuez, & Gunderson, 2010), another study revealed no such differences (Fitzpatrick & Kuo, 2015). Such inconclusive findings raise the question of under what conditions we can expect to see elevated emotional vulnerability in BPD.…”
Section: Research On Emotional Dysfunction In Bpdmentioning
confidence: 99%